Flower mites decrease nectar availability in the rain-forest bromeliad Neoregelia johannis - Guerra, Tadeu J.; Romero, Gustavo Q. [UNESP]; Benson, Woodruff W. (Cambridge University Press (CUP), 2010)
Nectarivorous flower mites can reduce the volume of nectar available to pollinators. The effects of the flower mite Proctolaelaps sp. on nectar availability in flowers of a melittophilous bromeliad Neoregelia johannis (Bromeliaceae) was evaluated in a coastal rain forest in south-eastern Brazil. In a randomized block experiment utilizing 18 flower pairs, one per bromeliad ramet, pollinators (Bombus morio) and mites were excluded, and then nectar volume, sugar concentration and sugar mass were quantified over the anthesis period. Mites significantly reduced nectar volume early in the morning (6h00-8h00), but not later (10h00-12h00). Mites decreased total volume of nectar available up to 22%. Sugar concentration in nectar was higher earlier in the morning, and decreased between 10h00-12h00. The pronounced consumption of nectar by mites during the period of higher sugar concentration reduced the total amount of sugar available to pollinators by 31%. This is the first study showing that flower mites decrease nectar rewards in a melittophilous plant. Because nectar volume by itself incompletely describes nectar production rates and the effects of nectar removal by flower mites on the availability of sugar, our study highlights the inclusion of sugar content in future studies assessing the effects of thieves on nectar production rates. Copyright © 2010 Cambridge University Press.
Keywords: Atlantic rain forest; Brazil; Bromeliaceae; Melicharidae; nectar thievery; sugar reward; coastal zone; entomophily; mite; monocotyledon; nectar; nectarivory; pollinator; rainforest; sugar; Acari; Bombus morio; Neoregelia; Proctolaelaps